A numerical investigation of mathematical modelling in 3D hexagonal porous prism on oil recovery using nanoflooding - Zafar, Mudasar; Hamzah, Sakidin; Sheremet, Mikhail; Iskandar, Dzulkarnain; Roslinda, Nazar; Al-Yaari, Abdullah; Nur Asyatumaila, Mohamad Asri; Mohd Zuki, Salleh; Bashir, Shazia (Elsevier Ltd, 2023)
The use of nanomaterials as a means of recovering heavy and light oil from petroleum reservoirs has increased over the preceding twenty years. Most researchers have found that injecting a nanoparticle dispersion (nanofluids) has led to good results and increased the amount of oil that can be recovered. In this research, we aim to imitate the three-dimensional hexagonal prism in the existence of SiO2 and Al2O3 nanoparticles for better oil recovery. Porosity (0.1≤φ≤0.4), mass flow rate (0.05mL/min≤Q≤0.05ml/min), nanoparticle concentration (0.01≤ψ≤0.04), and the effect of relative permeability (kr) on oil and water saturation in the presence of gravity under different time durations are all investigated. The result obtained for the model is verified with existing experimental data. The results indicated that the infulence of nanoparticle volume fraction (VF) is significant in enhancing the oil recovery rate. It is also observed that at low porosity values the oil recovery is maximum. The maximum oil recovery is attained at low values of mass flow rate in the 3D hexagonal prism in the presence of silicon and aluminium nanoparticles It is also observed that the use of SiO2 gives a better oil recovery rate than Al2O3. It is also observed that maximum oil recovery is obtained at 99% at a flow rate of 0.05 mL/min in the presence of silicon injection.